Neupogen (Filgrastim) Induced Acute Hematuria/Proteinuria with 3 Days of Use in a 7-Year-old Boy Diagnosed as Aplastic Anemia - Sohail Azam; Hassan Eliwan; Fatima Eltayeb Hago; Al Husein Mohammed Chyad Hammoudi (Dr. Sulaiman Al Habib Medical Journal)
Filgrastim, a granulocyte-colony stimulating factor (G-CSF), is used in patients with neutropenia caused by chemotherapy, bone marrow transplant, radiation poisoning, or any unknown etiology. It stimulates the bone marrow to increase the production of neutrophils. Although it has a good safety and efficacy profile, many patients experience different side effects ranging from mild symptoms such as abdominal pain, musculoskeletal pain, diarrhea, and headache, to severe symptoms/conditions such as splenic rupture, anaphylactic reaction, pulmonary hemorrhage, and hypoxia. Hematuria/proteinuria is one of the uncommon side effects seen in patient using Filgrastim for a longer period. However, to date there is no reported case of Filgrastim-induced hematuria with only 3 days of use. We report a case of a 7-year-old boy who developed hematuria with only three doses of Filgrastim and was diagnosed to have aplastic anemia.